War time : temporality and the decline of western military power - Rynning Sten (Insights : critical thinking on international affairs., 2021)
"A contributed volume, the book examines three interrelated dimensions of temporality related to war (trajectories, perceptions, and pace), and is a critical assessment of the evolution and future of Western military power"--